Malaysia Baru : réaménager la nouvelle dépendance du capitalisme malaisien à la Chine - Elsa Lafaye de Micheaux (Revue de la Régulation, 2019)
In the aftermath of the elections of May 9th 2018, the Federation of Malaysia entered a new era, the so-called Malaysia Baru. Unexpected and of deep historical significance, this political change, spearheaded by the 92 age-old leader Mahathir Mohamad, paved the way for the country’s sovereignty to be taken back from China. Under the previous Prime Minister Najib Razak, China, the new center of gravity in East Asia, had moved closer to Malaysia in all respects, at the risk of increased dependence — and with the corollary corruption and high public debt — without altering its institutional architecture. In this text, based on a field survey among the main economic administrations, we propose an account of the first reforms, focusing on the measures taken with regard to China. It appears that cooperation between the two countries is rapidly reconfiguring itself, but not moving towards a rift: the relationship is deepening within the framework of an adjusted and agreed upon dependence on China, while it is the Malaysian accumulation regime, dominated by the State and international integration resulting from the 1971 New Economic Policy, that could move toward a distribution of income less unfavorable to work.